2017
DOI: 10.4081/ozone.2017.6744
|View full text |Cite
|
Sign up to set email alerts
|

Use of oxygen-ozone therapy in the treatment of fibromyalgia

Abstract: Fibromyalgia (FM) is a pathology that is manifested by a spectrum of heterogeneous symptoms that are difficult to frame, from both a diagnostic and therapeutic point of view. On one hand, the clinical features are highly variable, and on the other, the pathophysiology has yet to be fully clarified. This paper aims to highlight how oxygen ozone -administered using a precise protocol from the Scientific Society of Oxygen Ozone Therapy -is able to act on several levels of the pathophysiology of FM by virtue of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In a case report published in 2017, MAH was applied twice a week to a 45-year-old female patient with FMS. In the components of the Fibromyalgia Survey Questionnaire, the Widespread Pain Index decreased from 15 to 7, and the Symptoms Severity Scale from 7 to 1 at the end of 12 sessions [20].…”
Section: Discussionmentioning
confidence: 95%
“…In a case report published in 2017, MAH was applied twice a week to a 45-year-old female patient with FMS. In the components of the Fibromyalgia Survey Questionnaire, the Widespread Pain Index decreased from 15 to 7, and the Symptoms Severity Scale from 7 to 1 at the end of 12 sessions [20].…”
Section: Discussionmentioning
confidence: 95%
“…Balestrero y cols. (2017) presentó el caso clínico de una paciente de 45 años quien, tras un total de 12 sesiones de autohemoterapia (2/semana por 6 semanas), presentó mejoría del dolor, el ánimo y la fatiga, evidenciado por el cuestionario FSQ (fibromyalgia survey questionnaire) (17). Bocci y Borreli (2002) trataron a 4 pacientes fibromiálgicos con autohemoterapia más CoQ10, disminuyendo los síntomas en las pacientes con FM (189.…”
Section: Discussionunclassified
“…For treating an acute and chronic pain syndrome, ozone is administered intraarticularly, intramuscularly, intrave� nously, subcutaneously, and even directly in intervertebral discs (intradiscally). 28,45,46 The routes o� o�ygen�ozone mi�� ture administration may vary over the course o� the treat� ment depending on the �eatures o� the pain syndrome and the disease course.…”
Section: Ozone Therapy Mechanismmentioning
confidence: 99%
“…Laboratory studies confirmed that high IL-8 levels were indeed associated with pain, while IL�6 concen� tration grew in cases o� hyperalgesia, e�cessive �atigue, and depression. 15 A team o� scientists led by Balestrero (2017) presented evidence of the efficacy of ozone therapy for treatment o� FM patients. They used treatment regimen based on Scientific Society of Oxygen Ozone Therapy Protocol (SIOOT), which involved influencing the process with the due account to pathogenetic �eatures o� FM.…”
Section: Why Do So Many Pathological Manifestations Exist?mentioning
confidence: 99%
See 1 more Smart Citation